ANALISIS ISI PESAN-PESAN DAKWAH DALAM BULETIN JUMAT MASJID RAYA BOGOR TAHUN 2018 - Sanra Wijaya; Elang Bahrudien (Jurnal Penelitian Multidisiplin Ilmu, 2022)
The very rapid development of technology in the information sector in the modern era is currently very helpful to human daily activities. The development of this information technology in addition to having a positive impact but also a negative impact on humans, for example, the many circulation of hoax news in the mass media such as on television, newspapers and internet media. In this case, the hoax news then causes negative things such as slander, gossiping, bringing into conflict in each other, and many others. Friday Bulletin of the Bogor Great Mosque in 2018 is a bulletin published every Friday as a medium to deliver da'wah messages in printed form. Just like the bulletin in general, the bulletin also has a management agency in it. The method of da'wah to the community is very necessary for the achievement of the objectives of da'wah. From the da'wah method it is necessary to make a da'wah pattern that makes the delivery of da'wah more effective. Based on the above context, the purpose of this study was (1) To analyze the contents of the da'wah messages in the Friday Bulletin of the Bogor Great Mosque in 2018. The messages of da'wah are in the form of da'wah messages of aqidah, morals, and sharia. (2) To find out what message is dominant in the 2018 Bogor Great Mosque Friday Bulletin. The methodology used in this study was a quantitative method with a descriptive content analysis approach. Data collection techniques were done through observation and documentation. The data was then used as research material. Meanwhile for sampling, a simple random sampling technique was used in this research. Furthermore, the data analysis stage was carried out to obtain valid results while for the reliable results was obtained by using the help of three competent judges in the field of da'wah. Based on the results of the analysis of the data collected, the researcher obtained the results regarding the da'wah messages as follows, (1) Da'wah messages contained in the Friday Bulletin of the Bogor Grand Mosque in 2018 include: aqidah messages, moral messages, and Shari'a messages. The contents of the message in the bulletin include sentences and paragraphs containing the da'wah messages contained in the Bogor Great Mosque Friday Bulletin in 2018. (2) Moral messages are the highest in the 2018 Bogor Great Mosque Friday Bulletins with a percentage of 41%. Furthermore, the Shari'a message ranks second with a percentage of 34.4%, while the aqidah message is the last in the Friday Bulletin of the Bogor Great Mosque in 2018 with a percentage of 24.6%. From the results of the study, it was known that the moral message was the most dominant message percentage in the Bogor Great Mosque Friday Bulletin in 2018.